MRI arterial spin labeling in evaluating hemorrhagic transformation following endovascular recanalization of subacute ischemic stroke - Wu, Liheng; Liu, Yanghui; Zhu, Liangfu; Li, Tianxiao; Wang, Li’na; Zhang, Yang; Zhou, Zhilong; Xing, Ying; Wang, Meiyun; Gao, Bulang (Frontiers in Neuroscience, 2023)
Objective To investigate the value of the MRI arterial spin labeling (ASL) in evaluating the blood-brain barrier permeability of anterior circulation ischemic lesions in subacute ischemic stroke (SIS) and the risk of hemorrhage transformation (HT) after endovascular recanalization. Materials and methods Patients with anterior circulation SIS treated with endovascular recanalization were prospectively enrolled. The imaging presentations in the MRI ASL sequences, dynamic contrast-enhanced (DCE) sequence, and Xper CT were studied. The relative cerebral blood flow (rCBF), volume transfer constant (Ktrans), and the weighted Kappa coefficient (rKtrans) were analyzed. Results Among 27 eligible patients, HT occurred in 7 patients (25.92%). Patients with HT had significantly higher rCBF value (1.56 ± 0.16 vs. 1.16 ± 0.16), Ktrans, (0.08 ± 0.03 min vs. 0.03 ± 0.01 min) and rKtrans (3.02 ± 0.89 vs. 1.89 ± 0.56). The ASL imaging sequence had a high consistency with the DCE sequence and Xper CT with a high weighted Kappa coefficient of 0.91 for the DCE sequence and 0.70 for the Xper CT imaging. The DCE sequence was also highly consistent with the Xper CT in imaging classification with a high weighted Kappa coefficient of 0.78. The rCBF value in the 21 patients with the subcortical and basal ganglia infarction was significantly lower than that in the other 6 patients with the cortical infarction (1.222 ± 0.221 vs. 1.413 ± 0.259, t = 1.795, P = 0.004). Conclusion The MRI ASL sequence has an important role in evaluating the blood-brain barrier permeability and the risk of hemorrhagic transformation of anterior circulation SIS following endovascular recanalization.